Radicalism and Maritime Piracy: Comparing the Gulf of Guinea and Gulf of Aden - Saripudin, Mohamad Hery (Universitas Komputer Indonesia, 2025)
Sea piracy in the Gulf of Aden (GoA) and Gulf of Guinea (GoG) is closely linked to radical groups operating in both regions. While the connection between Al-Shaabab and Somali Pirates is clear, the indirect effects of Boko Haram and Islamic State of West Africa (ISWAP) to the GoG related countries such as Nigeria and Cameroon is not well explored. Therefore, this study aims to conduct a comparative analysis to reveal how radicalism affects maritime security in the GoA and GoG through distinctly different mechanisms. In Somalia, Al-Shabaab’s direct involvement with Somali pirates creates a more manageable, albeit concentrated threat. Conversely, ISWAP and Boko Haram in Nigeria and Cameroon generate complex, multi-layered security challenges by disrupting both governmental security priorities and community-level stability, creating an indirect yet profoundly powerful impact on escalating incidents in the Gulf of Guinea. As a result, radicalism's negative impact in the GoA is more direct and manageable, in contrast to the GoG, which is more complex and requires a more comprehensive approach. Keywords— Al-Shabaab, Boko Haram, Gulf of Aden, Gulf of Guinea, ISWAP, Maritime piracy, radicalism